O direito fundamental à proteção de dados pessoais e a (i)licitude do compartilhamento de dados de aposentados com empresas de crédito no Brasil - Caetano, Fernando José Resende (2023)
The theme of the research is to analyze the effectiveness of the fundamental right to the protection of personal data regarding the sharing of personal data of elderly people with credit companies in Brazil. The research sought to analyze the following problem: how does the sharing of personal data, by the INSS, of elderly retirees and pensioners with financial institutions, exacerbating the hypervulnerability of such consumers and affronting the human dignity of such individuals? What measures can be taken to prevent this damage? The general objective of the research is to verify the worsening of the vulnerability of elderly consumers due to the way their personal data is processed by the INSS, aiming to adapt it to the fundamental right to privacy and privacy, in addition to proposing mechanisms to protect their data. consumers in relation to financial institutions. The research uses the inductive method of approach (analysis from the particular to the general), with a view to building a reasoning based on premises, seeking a true conclusion. The theoretical framework of the research is the theory of the “dialogue of sources”, developed in Brazil by Claudia Lima Marques, based on the teachings of Erik Jayme. It is concluded that the violation of personal data protection can cause exposure to abusive commercial practices and over-indebtedness. Measures to prevent damage resulting from the violation of the fundamental right to the protection of personal data of elderly people involve: (i) the creation of laws that prohibit active telemarketing to this public and that prohibit the sharing of personal data with private entities for purposes to offer products and services; (ii) the adoption of a compliance model for the protection of personal data by the Public Administration; (iii) the efficient performance of the ANPD and the bodies that make up the SNDC in the activities of inspection and sanctioning of data processing agents, as well as in suggesting the adoption of standards and good practices for the processing of personal data.